Saints et rois: la genèse du politique au Maroc - Rhani, Zakaria (Anthropologica, 2022)
In this paper, I consider the question of politics and political symbolism in Morocco. Starting from an analysis of a myth I collected during my ethnographic research in mid-west Morocco, I will propose some basic hypotheses for understanding the genesis of Moroccan politics. I will show, inter alia, how religious and political symbols are indissociable. The king as political sovereign is also presented as a saint; the saint, supreme religious symbol, also asserts himself as a potential king. Saints and kings are the two extreme figures of Moroccan political history. The myth appears, in the end, to be an ad hoc commentary on the fundamental bases of Moroccan identity.